STRENGTHENING EFL LEARNERS’ WRITING COMPETENCIES THROUGH THE DECENT EMPLOYMENT OF QUILLBOT - Kristian Florensio Wijaya (Widya Mandala Surabaya Catholic University, 2025)
ABSTRACT Technology plays a crucial role in strengthening EFL learners’ writing proficiency levels. As multifaceted feedback provisions are constantly addressed, the long-term nurturance of writing competencies growth can be ensured. This small-scale library study employed a thematic analysis while reviewing some significant findings of 30 previously published studies of QuillBot application benefits in empowering EFL learners’ writing skills development. The researcher capitalized on a thematic analysis approach to yield more accurate, believable, and relatable data as each prior finding was categorized into some major identical themes. The thematically-subsumed findings suggested that second language educators commence their regular writing learning enterprises with the meaningful internalization of the QuillBot application, in which EFL learners can transform into more positive and skillful writers. Keywords: Technology; QuillBot; EFL learners; library study; thematic analysis